INFLUENCE SERVICE QUALITY, TOURISM POWER, DESTINATION IMAGE, AND PRICES ON VISITOR SATISFACTION IN PUNCAK MAS LAMPUNG TOURISM OBJECT - Berliana, Afifah; Djuardi, Dian Komarsyah; Nugeraha, Prasetya (Jurnal Kompetitif Bisnis, 2022)
Visitors to Puncak Mas Lampung tourism object can be increased through the development of models of service quality, tourist attraction, destination image and price. The independent variables in this study are service quality, destination image, and price. The data of this study is primary data obtained from the sample by collecting 100 respondents using non-probability sampling with purposive sampling technique. The results of the analysis test that: partially the quality of service and tourist attraction does not have a significant effect on visitor satisfaction at the Puncak Mas Lampung tourist attraction partially, partially the destination image and price have a significant effect on visitor satisfaction at the Puncak Mas Lampung tourist attraction, and simultaneously the image of the destination and price has a positive and significant effect on visitor satisfaction at Puncak Mas Lampung tourism object.